2012
DOI: 10.1128/cvi.05583-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus K(HML-2) Gag- and Env-Specific T-Cell Responses Are Infrequently Detected in HIV-1-Infected Subjects Using Standard Peptide Matrix-Based Screening

Abstract: T-cell responses to human endogenous retrovirus (HERV) K(HML-2) Gag and Env were mapped in HIV-1-infected subjects using 15mer peptides. Small peptide pools and high concentrations were used to maximize sensitivity. In the 23 subjects studied, only three bona fide HERV-K(HML-2)-specific responses were detected. At these high peptide concentrations, we detected falsepositive responses, three of which were mapped to an HIV-1 Gag peptide contaminant. Thus, HERV-K(HML-2) Gag-and Envspecific T-cell responses are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…While HERV-K(HML-2) RNA appears to be readily detected in all tissues, including the thymus (33), we are of the position that the expression of HERV-K(HML-2)-Gag and -Env protein has not been convincingly demonstrated in any healthy adult human tissue, despite extensive screening (30). The fact that we are not able to more readily detect T cell responses to these antigens in HIV-1-infected individuals using 15-mers may be indicative of tolerance (29). Alternatively, however, since our data indicate very low levels of HERV-K(HML-2) antigen expression as compared with HIV-1 antigen expression, and since the expression of the two would be tightly associated, it is possible that T cells specific for the former are simply not able to effectively compete for priming by DCs.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While HERV-K(HML-2) RNA appears to be readily detected in all tissues, including the thymus (33), we are of the position that the expression of HERV-K(HML-2)-Gag and -Env protein has not been convincingly demonstrated in any healthy adult human tissue, despite extensive screening (30). The fact that we are not able to more readily detect T cell responses to these antigens in HIV-1-infected individuals using 15-mers may be indicative of tolerance (29). Alternatively, however, since our data indicate very low levels of HERV-K(HML-2) antigen expression as compared with HIV-1 antigen expression, and since the expression of the two would be tightly associated, it is possible that T cells specific for the former are simply not able to effectively compete for priming by DCs.…”
Section: Discussionmentioning
confidence: 85%
“…HERV-K(HML-2)-Env-and Gag-specific T cell responses detectable by 15-mer peptides are rare (29). Hence, to generate additional HERV-K(HML-2)-specific T cell clones we screened subjects using optimal HERV-K(HML-2) determinants identified in our previous studies (25)(26)(27).…”
Section: Cross-reactive Hiv-1/herv-k(hml-2)-specific T Cells Exist Anmentioning
confidence: 99%
“…Further, HERV-K (HML-2) encodes two putative oncogenes, rec and np9 (5,13,101), either of which might play a role in HIVrelated malignancies. However, it has recently been shown that HERV-K antigens promote a T cell response against HIV-1 (50, 123), although Gag-and Env-specific T cell responses are infrequent (65). Thus, increased expression of HERV-K (HML-2) following HIV-1 infection might actually be helpful in controlling the replication of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Gag has been seen in the peripheral blood cells of leukemia patients [12] and also in prostate cancer and ovarian cancer but not in healthy donors [13], [14]. Furthermore, it has been reported that HIV infection leads to increased expression of HERVs, and T cell responses to HERV peptides have been detected in HIV-1-infected patients [15], [16], [17], [18], [19], [20]. Individuals who control HIV-1 viremia without highly active antiretroviral therapy (HAART) had stronger and broader HERV-specific T cell responses than HAART-suppressed patients, virologic noncontrollers, immunologic progressors, and uninfected controls.…”
Section: Introductionmentioning
confidence: 99%